Human Bocavirus 1 Primary Infection and Shedding in Infants - Martin, Emily T. (J Infect Dis, 2015)
Background. Human bocavirus 1 (HBoV-1) is frequently detected in young children. The role of HBoV-1 in respiratory illness is unclear, owing to frequent detection in asymptomatic children. Methods. Weekly oral fluid samples from a longitudinal cohort of infants were tested by quantitative polymerase chain reaction for HBoV-1 DNA. Symptoms during HBoV-1 primary shedding events were compared to those during 14-day control periods occurring 1 month prior to and following the primary event. Eight single-nucleotide polymorphisms were analyzed to assess HBoV-1 variants. Results. Sixty-six of 87 children (76%), followed for at least 18 months from birth, had a primary HBoV-1 infection. HBoV-1 was consistently detected for >1 month (maximum duration, 402 days) following 42 of 66 primary shedding events. Children were more likely to experience new cough symptoms (odds ratio [OR], 2.7; 95% confidence interval [CI], 1.4–5.5) and to visit a healthcare provider (OR, 2.8; 95% CI, 1.02–7.7) during the 14 days surrounding the time of initial detection of HBoV-1. Recurrent HBoV-1 shedding events were found in 33 children (50%). Twelve of 48 children with HBoV-1 variant data had multiple viral allelic patterns over time. Conclusions. HBoV-1 primary shedding events are associated with mild respiratory illness with subsequent prolonged detection of HBoV-1 DNA for up to a year. HBoV-1 reinfection contributes to long-term shedding.